Pengaruh Sosialisasi Cara Pemanfaatan Perpustakaan Terhadap Peningkatan Keterampilan Pemustaka dalam Pemanfaatan Koleksi Perpustakaan Universitas Bengkulu - Elnadi, Isran (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2019)
Tanggapan responden adanya fasilitas locker (57%), responden belum mengerti penggunaan OPAC (21%), responden mengerti cara penelusuran OPAC (57%), responden belum memahami penggunaan internet (47%), responden yang  mengerti penelusuran internet (23%), yang sudah mengerti (30%), subyek dan pengarang responden belum memahami (41%), sedangkan pustaka yang memahami menelusur koleksi di rak, melalui judul, subyek dan pengarang (34%), responden yang mengetahui adanya foto kopi (27%), yang belum memahami adanya foto kopi (46%).  Pemustaka yang mengerti tentang tatip pinjam kembali bahan pustaka (14%), yang belum memahami (51%), responden yang paham dan memanfaatkan ruang baca (64%) karena suasananya menyenangkan, untuk hak dan kewajiban respon memberikan tanggapan (69%) artinya baik, antara pustakawan dan pemustaka berkomunikasi dengan baik dan harmonis, sedangkan yang mengerti layanan rujukkan (60%) responden belum paham, (17%), paham sekali akan adanya layanan rujukkan(23%), sedangkan responden belum memahami sosialisasi lingkungan (57%), artinya pustakawan perlu mengadakan bimbingan pemustaka agar mengenal lokasi perpustakaan. This studyis about the influence of socialization on how to use the library to improve users’skillsin the usage of the collection at UNIB library. The aim of this study is to analyze users’ skillsto find information in the library, and to know barriers faced by users to use the library’s facilities provided by UNIB library. The respondent of this research was 7 faculties, every faculties was took 10 students as the samples. There are two data used in this study; primary and secondary data. The primary data come from questionnaire survey, and the secondary data is supporting data from the interview and observation. The reaction of respondent about locker facility is 57%, the respondent not understand the usage of OPAC is 21%, the respondent that understand the usage of OPAC is 57%, confuse the usage of internet is 47%, understand the usage of internet is 23%, the respondent know how to search the collection in the shelf, including title, subject and author 34%, respondent know there is an photo copy is 27% and not 46%. The respondent that know the role of borrow and return the books 14%, do not know 51%, the respondent that know how to use library 64% because have good situation, for the right and the users’ obligation in the library, the respondent gives 69%. Understand the reference of service is 60% and not 17%, very understand the reference of service 23%, and the respondent still confused of socialization of environment in the library is 57%, its mean the librarians should guiding the user so that the user of library know every room of the library.